The Influence of the Group Investigation Type Cooperative Learning Model on the Critical Thingking Skills of Grade XI Geography Students - Warahma, Mifta; Susetyo, Onwardono Bigharta Bekti (Global Action and Education for Society, 2025)
This study aims to examine the influence of the Group Investigation (GI) cooperative learning model on the critical thinking skills of grade XI geography students at Semen Padang High School. The research was driven by the observation that students demonstrated low levels of critical thinking, as reflected in their difficulties in expressing opinions, analyzing issues, and drawing logical conclusions during geography lessons. Employing a quantitative approach with a quasi-experimental design and a non-equivalent control group, the study involved all grade XI students, with class XI.1 assigned as the experimental group and class XI.3 as the control group, each comprising 31 students selected through purposive sampling. The instrument used was a critical thinking test developed based on Ennis’s indicators, which include: (1) providing simple explanations, (2) building basic skills, (3) making inferences, (4) providing further explanations, and (5) developing strategies and tactics. Data were analyzed through normality testing and an independent sample t-test. The findings revealed that the experimental group achieved a higher mean score (0.225) compared to the control group (0.585). Furthermore, the t-test result showed a significance value of 0.001 < 0.05, indicating that the application of the GI model had a significant positive effect on students’ critical thinking skills. Therefore, it can be concluded that the Group Investigation model is an effective instructional approach for enhancing students’ critical thinking in geography learning.